Comparative analysis of hysterectomy types and approaches on oncological survival in 2023 FIGO stage II endometrial carcinoma - Jianhao Sun; Zhenzhen Wu; Jiayu Chen; Qinglei Hang; Yaqin Zhao; Juan Li; Jie Huang; Xiaoli Zhao; Ji Xia; Xinjuan Jiao; Qing Liu; Dan Lu (BMC Surgery)
Abstract Background The objective is to investigate the relationship between the type and approaches of hysterectomy and the oncological survival outcomes in women diagnosed with stage II endometrial carcinoma (EC), as classified by the 2023 International Federation of Gynecology and Obstetrics (FIGO) staging system. Methods A retrospective analysis was conducted on patients with 2009 FIGO early-stage (stages I and II) EC who underwent surgical treatment between 2018 and 2019. These patients were reclassified in accordance with the 2023 FIGO staging system, and those diagnosed with stage II EC under this system were selected as the study population. A non-inferiority test was employed for the analysis, with disease-free survival (DFS) serving as the primary outcome measure. DFS was evaluated using Kaplan-Meier curves, and comparisons were conducted through the log-rank test. Result A cohort of 288 patients diagnosed with early-stage EC according to the 2009 FIGO staging system were re-evaluated and reclassified. Ultimately, the study encompassed a cohort of 80 patients diagnosed with stage II EC, as classified according to the 2023 FIGO staging system. 52 individuals underwent radical hysterectomy or modified radical hysterectomy (RH/mRH), while 28 patients received a simple hysterectomy (SH). The 5-year DFS was 84.62% for the RH/mRH group vs. 92.86% for the SH group (difference, 8.24% [95% CI, -5.44–21.92%]), which met the noninferiority criterion. Between the groups, the difference in 5-year DFS (p = 0.255) was not statistically significant. The laparoscope group comprised 62 cases, whereas the laparotomy group consisted of 18 cases. Between the groups, the difference in 5-year DFS (88.55% versus 83.33%, p = 0.538) was not statistically significant. This finding aligns with our observations of patients diagnosed with 2009 FIGO Stage II EC. Conclusion In comparison to SH, RH/mRH did not confer a survival advantage for patients diagnosed with 2023 FIGO stage II EC.